BRIDGING THE GAP: TEACHERS’ KNOWLEDGE AND APPLICATION OF AI-DRIVEN LEARNING PLATFORMS IN STEM-BASED ENGLISH LANGUAGE EDUCATION - Wahyunengsih, Wahyunengsih (English Review: Journal of English Education, 2025)
This study aims to determine teachers' knowledge level about AI-driven learning platforms in STEM education, to determine the extent to which language teachers apply AI-driven learning platforms in STEM education, and to see whether the level of knowledge, attitudes and readiness of teachers is balanced with its application. This study uses a quantitative and qualitative design or mixed method and applies a correlation approach. The participants of this study involved 33 English teachers in Indonesia. The results of this study conclude that the level of knowledge of language teachers on AI-driven platforms in STEM learning is still classified as intermediate. The application of AI-driven platforms in STEM learning for English teachers is also in the intermediate category. Language teachers have not yet entered the high level of application of AI-driven platforms in STEM learning, although a small number of teachers can reach this level. The correlation between teacher knowledge of AI-driven platforms in STEM learning is directly proportional to their application in learning practices. However, the data shows no correlation between teacher attitudes and readiness towards AI-driven platforms in STEM learning and the application of AI-driven platforms in STEM learning.